Pengaruh Penggunaan Platform Ruangguru terhadap Motivasi Belajar Luring pada Mata Pelajaran Bahasa Indonesia di Lingkungan Universitas Pendidikan Indonesia - Moh. Reza Akmal Fadhillah; Muhammad Fadli Putra Riyanto; Muhammad Gathan Alfarouk; Rifki Wildan (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to see to what extent the use of the Ruangguru platform affects students' learning motivation in offline Indonesian language learning at the Indonesian Education University. Amid the rapid development of educational technology, it is important to understand the role of digital tools such as Ruangguru in the context of face-to-face learning. This study uses a quantitative approach by distributing questionnaires to 102 students who have used Ruangguru and are at least 15 years old. The results show that most aspects of platform use are classified as low, but elements such as attractiveness of appearance, presentation of materials, and quality of learning videos are quite appreciated by users. Students' learning motivation is in the fairly high category, especially in terms of enthusiasm for learning and self-confidence in understanding the material. The habit of using the platform routinely is still relatively low. These findings indicate that Ruangguru has the potential to support offline learning motivation, but its effectiveness will be more pronounced if accompanied by direct direction from lecturers and more structured learning strategies.